The Paris Agricultural Show assistance for African exhibitors - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Every year Paris becomes the centre of the world of agricultural machinery. For ten days In March, the Paris Agricultural Show attract-s many thousands of visitors. Like its other European counterparts, the Show is a show case of technical progress...